3,3′-Dimethyl-1,1′-methylenediimidazolium dibromide - Jie Liu; Xilian Wei; Zengbin Wei; Jiuqiang Liu; Liqiang Zheng (Acta Crystallographica Section E, 2009)
In the crystal structure of the title compound, C9H14N42+·2Br−, the cation and anions have crystallographic mirror symmetry, with the mirror plane running through the central CH2 group for the cation. The latter are stacked along the a axis, forming channels hosting the bromide anions. The crystal packing is stabilized by C—H...Br hydrogen-bonding interactions, generating a two-dimensional network.